2020
DOI: 10.21203/rs.3.rs-48875/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinicopathological features of Epstein-Barr virus infection, microsatellite instability, tumor mutation burden and PD-L1 status in Chinese patients with gastric cancer

Abstract: Objectives: Gastric cancer (GC) is the 4th most common type of cancer worldwide. Different GC subtypes exhibit unique molecular features that may potentially guide therapeutic decisions. The aim of the present study was to investigate Epstein-Barr virus (EBV) infection, microsatellite instability (MSI) status, the expression of programmed death-ligand 1 (PD-L1) and gene mutations in patients with surgically-treated GC. Methods: The data of 2,504 GC patients, who underwent potentially curative gastrectomy with … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…The mutation of the DDR gene in cancer cells is usually associated with the increased expression of PD-1/ PD-L1 genes within the TME [56,64,233,234], such as the DSB repair gene [221], MMR gene [146,235,236] and RB1 [171,237]. The expression of BER/SSBR has been shown to be negatively correlated with the level of PD-L1 observed in cancer cells [150,235].…”
Section: Abnormal Ddr Pathway and Immune Checkpoint Moleculesmentioning
confidence: 99%
“…The mutation of the DDR gene in cancer cells is usually associated with the increased expression of PD-1/ PD-L1 genes within the TME [56,64,233,234], such as the DSB repair gene [221], MMR gene [146,235,236] and RB1 [171,237]. The expression of BER/SSBR has been shown to be negatively correlated with the level of PD-L1 observed in cancer cells [150,235].…”
Section: Abnormal Ddr Pathway and Immune Checkpoint Moleculesmentioning
confidence: 99%
“…Therefore, in intestinal-type neoplasms of the vulva, a gene panel test may be helpful to select treatment options. In addition, while present case was microsatellite stable, some reports have shown that microsatellite instability-high and mismatch repair deficiency is more frequent in gastric adenocarcinoma of intestinal-type [54,55], and microsatellite status and IHC for mismatch repair protein may also be checked in intestinal-type neoplasms of the vulva.…”
Section: Discussionmentioning
confidence: 51%
“…Kakiuchi et al, 25 Birkman et al, 60 Machado et al 73 RhoA Mt (0%) Mt (15-25%) Cancer Genome Atlas Research Network, 18 Kakiuchi et al, 25 Wang et al 74 ARID1A Mt (12-16%) Mt (9-15%) Kakiuchi et al, 25 Wu et al, 75 Garcia-Pelaez et al 76 Claudin 18.2 OverExp (15-46%) OverExp (28-75%) Sahin et al, 77 Dottermusch et al, 78 Pellino et al, 79 Coati et al 80 MSI-H /dMMR 4-10% 0-4% Kim et al, 55 Birkman et al, 60 Zhang et al 81 EBV 1-9% 0-4% Kim et al, 55 Birkman et al, 60 Zhang et al 81 PD-L1* OverExp (28-65%) OverExp (19-54%) Fukamachi et al, 82 Liu et al, 83 CDH1 is a tumor suppressor gene that codes for E-cadherin, which is a calcium-dependent transmembrane glycoprotein that forms the adherens junction via the extracellular domains, connects to the cytoskeleton via the cytoplasmic domains, and mediates cellular signaling. 85 Loss of its function confers diffused cellular morphology, migratory and invasive abilities, metastasis, and the EMT process.…”
Section: Cdh1mentioning
confidence: 99%